The Protein-Energy Synchronization Index of The Tropical Legumes for Ruminants - Afduha Nurus Syamsi; Merryafinola Ifani; Yusuf Subagyo (State Islamic University of Sultan Syarif Kasim Riau, 2022)
ABSTRACT. The study was aimed to assess protein-energy synchronization (PES) index of the tropical legumes as feed for ruminants. The research was carried out experimentally in two stages. The first stage was measured the nutritional value of legumes using the proximate method. All types of legumes had been dried (at 600C for 3 days) and grinded. The second stage is to calculate the PES index based on the average degradation of g protein and Kg of organic matter (OM) per hour for each legume. Protein degradation and OM were measured at 2, 4, 6, 8, 12, 24, 48, and 72 hours of observation. The results of the degradation observations at each hour were analyzed by linear regression to obtain the average degradation per hour, then the results were included in the calculation formula of the PES index. The PES index of each legume was discussed descriptively. The analysis showed that legume is a source of fiber with an average crude fiber of 18% and a high protein content of 23.23%. Based on the calculation of the PES index Leucaena leucocephala (0.34) and Calliandra calothyrsus (0.31) are at a low level, while Indigofera (0.48), Sesbania grandiflora (0.42), and Gliricidia sepium (0.47) are at the medium level. This difference was caused by differences in the rate of degradation of protein and organic matter of each legume, besides the presence of antinutrients greatly affected the resulting PES index. The research concluded that the tropical legumes in ruminant feed has the PES indexes at low to medium levels.